Effects of Sex and Event Type on Head Impact in Collegiate Soccer - Reynolds, Bryson B. (Orthop J Sports Med, 2017)
BACKGROUND: The effects of head impact in sports are of growing interest for clinicians, scientists, and athletes. Soccer is the most popular sport worldwide, but the burden of head impact in collegiate soccer is still unknown. PURPOSE: To quantify head impact associated with practicing and playing collegiate soccer using wearable accelerometers. STUDY DESIGN: Descriptive epidemiological study. METHODS: Mastoid patch accelerometers were used to quantify head impact in soccer, examining differences in head impact as a function of sex and event type (practice vs game). Seven female and 14 male collegiate soccer players wore mastoid patch accelerometers that measured head impacts during team events. Data were summarized for each athletic exposure, and statistical analyses evaluated the mean number of impacts, mean peak linear acceleration, mean peak rotational acceleration, and cumulative linear and rotational acceleration, each grouped by sex and event type. RESULTS: There were no differences in the frequency or severity of head impacts between men’s and women’s soccer practices. For men’s soccer, games resulted in 285% more head impacts than practices, but there were no event-type differences in mean impact severity. Men’s soccer games resulted in more head impacts than practices across nearly all measured impact severities, which also resulted in men’s soccer games producing a greater cumulative impact burden. CONCLUSION: Similar to other sports, men’s soccer games have a greater impact burden when compared with practices, and this effect is driven by the quantity rather than severity of head impacts. In contrast, there were no differences in the quantity or severity of head impacts in men’s and women’s soccer practices. These data could prompt discussions of practical concern to collegiate soccer, such as understanding sex differences in head impact and whether games disproportionately contribute to an athlete’s head impact burden.